Analisis Faktor yang Memengaruhi Penyakit Hipertensi pada Lanjut Usia (LANSIA) di wilayah Kerja Puskesmas Dabun Gelang Kota Aceh - Erna Khairani; Ismail Efendi; Ramadhanni Syafitri Nasution (Pusat riset dan Inovasi Nasional, 2025)
Hypertension is a non-communicable disease that can be life-threatening, especially in the elderly. According to the WHO, more than 15 million people aged 30–69 years die each year from non-communicable diseases. This study aims to analyze factors influencing the incidence of hypertension in the elderly, including smoking, stress levels, culture, diet, exercise, and coffee drinking habits. This research method used a quantitative approach with a cross-sectional design. The population was 738 elderly people, with a sample size of 259 elderly people, and random sampling was used. Data analysis was performed using univariate, bivariate using the Chi-Square test, and multivariate using the Pearson correlation test. The results of this study such as Smoking with hypertension: There is a significant influence (p = 0.002), stress level There is a significant influence (p = 0.002), Culture There is a significant influence (p = 0.010), Eating patterns with hypertension are significant (p = 0.049), Exercise There is a significant influence (p = 0.003), drinking coffee with a significant influence (p = 0.048). Multivariate analysis shows that culture (p = 0.003; r = 0.177) and coffee drinking habits (p = 0.022; r = 0.139) are the most influential factors on elderly hypertension, while other factors are not significant. This study shows that smoking, stress levels, culture, diet, exercise, and coffee consumption are significantly associated with hypertension in the elderly. However, a multivariate analysis revealed that cultural factors and coffee drinking habits were the most dominant factors influencing hypertension, while other factors had no significant effect after being controlled for. Therefore, efforts to prevent and control hypertension in the elderly need to focus on changing cultural practices that are less conducive to health and regulating coffee consumption, while still considering the implementation of a healthy lifestyle overall.